Pengaruh Edukasi Gizi Pengaruh Edukasi Gizi Audio Visual Terhadap Pengetahuan Gizi dan Persepsi Body Image Siswa SMPN 1 Tilango: Studi Quasi-Eksperimen Pretest–Posttest dengan Kelompok Kontrol - Farlin Usman; Sunarto Kadir; Yoyanda Bait (Universitas Pahlawan Tuanku Tambusai, 2026)
Nutrition education plays a crucial role in improving adolescent nutritional literacy and helping them develop healthier eating patterns. Audio-visual media is considered more effective than traditional methods because it presents information visually and audibly, making the material easier to understand and remember, including in shaping perceptions of body image. This study aimed to measure the effect of audio-visual-based nutrition education on nutritional knowledge and body image perceptions of students at SMP Negeri 1 Tilango. The study used a quantitative approach with a quasi-experimental pretest-posttest and control group design. A total of 60 students were divided into two groups: the intervention group with audio-visual media and the control group with leaflets. Analysis was performed using the Wilcoxon Signed-Rank Test, Paired Sample T-Test, and Mann-Whitney test. The results showed a significant improvement in the audio-visual group, with average nutritional knowledge increasing from 65.3 to 85.7 (p=0.001) and body image perception from 58.4 to 80.2 (p=0.002). The leaflet group also experienced a smaller increase in knowledge, from 64.9 to 75.1 and body image perception from 57.9 to 68.3 (p<0.05). A comparison of the two groups indicated that audiovisual media was more effective in improving nutrition knowledge (p=0.01) and body image perception (p=0.03). This study confirms that audiovisual media is a more engaging and easily understood educational tool, making it suitable for use by schools and health professionals to improve nutrition understanding and body image perception in adolescents. Keywords: Nutrition Education, Audiovisual Media, Nutrition Knowledge, Perception, Body Image